ANALISIS STRATEGI MARKETING MIX UNTUK MENARIK MINAT JEMAAH UMRAH DI PT. QIBLATAIN SAFARINA BAKTI GENDING - Nur Syamsiyah; Fitri Fahilatul Umroh (I'THISOM : Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the application of marketing mix strategies in attracting Umrah pilgrims at PT Qiblatain Safarina Bakti. This research uses descriptive qualitative methods with data collection techniques through interviews, observation, and documentation. The results showed that the marketing mix strategy which includes product, price, place, and promotion has a significant influence in increasing the number of pilgrims. Variety and quality products, competitive prices, strategic location, and effective promotion through digital media and direct interaction with the community are the main factors in the success of the company's marketing strategy. Nevertheless, price competition with other travel agencies is the main challenge that PT Qiblatain Safarina Bakti must face. Therefore, the company needs to continue to innovate in services, strengthen promotional strategies, and maintain service quality to remain competitive in this field.